The Conflict in Goma: An Analysis of the M23 Rebellion and its Implications - Ndomba, Monique; Trefon, Theodore; Kabuyaya, Noël (European Journal of Applied Sciences, 2025)
The eastern region of the Democratic Republic of Congo (DRC) has been a focal point of conflict for decades, with the recent resurgence of the March 23 Movement (M23) exacerbating instability. This article provides a comprehensive analysis of the M23 rebellion, focusing on its historical context, the capture of Goma, and the ensuing humanitarian crisis. The study examines the roles of regional actors, particularly Rwanda, and the international community’s response to the escalating conflict. Through this analysis, the article aims to shed light on thecomplex dynamics at play and the potential pathways to sustainable peace in the region.